2013
DOI: 10.1039/c2fo30111c
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of amyloid-β 1-42 structure and toxicity by proline-rich whey peptides

Abstract: A proline-rich peptide product prepared from bovine whey protein that was enriched in several hydrophobic amino acids including proline (whey proline-rich peptide, wPRP) was shown to modulate the folding pathway of human amyloid beta peptide 1-42 (Ab42) into oligomers. Concentrationdependent changes in ThT-binding to Ab42 by wPRP indicated suppression of oligomerisation, that was supported by Transmission Electron Microscopy. Suppression of b-sheet and specifically, antiparallel b-sheet structures by wPRP was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 71 publications
(97 reference statements)
0
20
0
Order By: Relevance
“…The link between antiparallel β structure and oligomer toxicity is more and more documented in literature. For instance, it was shown by ATR-FTIR that whey proline-rich peptides suppressed both oligomerization and the formation of antiparallel β-sheet (Bharadwaj et al, 2013), leading to a rescue of yeast and neuronal cells. Such modulation of the folding pathway of Aβ 1-42 has also been shown for Fucosterol, which protected neuronal cells against Aβ 1-42 -induced toxicity (Gan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The link between antiparallel β structure and oligomer toxicity is more and more documented in literature. For instance, it was shown by ATR-FTIR that whey proline-rich peptides suppressed both oligomerization and the formation of antiparallel β-sheet (Bharadwaj et al, 2013), leading to a rescue of yeast and neuronal cells. Such modulation of the folding pathway of Aβ 1-42 has also been shown for Fucosterol, which protected neuronal cells against Aβ 1-42 -induced toxicity (Gan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight the major role of the major histocompatibility complex in DIE, whereas additional risk factors for benign eruption may play a role in 6% of the population. In conclusion, for certain drugs and particular populations, screening patients HLA haplotype before drug introduction could be used to reduce DIE occurrence ( 29 ).…”
Section: Pathophysiologymentioning
confidence: 99%
“…14 Similarly, proline-rich hydrophobic peptides have been found to alter Aβ 1-42 folding and fibril formation. 20 . Seminal work in AD indicated that tachykinin neuropeptides possess the ability to ameliorate the neurotoxic effects of Aβ peptides.…”
Section: Introductionmentioning
confidence: 99%